Inte bara producent för gästens upplevelse utan även för den egna : Hur Piteå Summer Games lagvärdsutbildning kan använda sig av upplevelseproduktion - Karlström, Malin (2014)
Piteå Summer Games is one of the largest international football tournaments for youths and children in Europe and the second largest in Sweden. The tournament has been played every year since the start in 1990. At present, 1650 non-profit volunteers spread out over different responsibility groups are needed to make the tournament happen. One of these is the host group, in charge of guiding the teams from non-Scandinavian countries. The last few years it has been difficult to fulfill the tournament goal that every team host should take care of no more than one team, and that they should have the language competence to interact with the members of the team in their native language. An education, with start in 2014, is being set up for the team hosts in order to improve the organization around them. The education will be conducted by two previous hosts with many years of experience within the tournament. The purpose of this essay is to develop a concept for Piteå Summer Games and their coming team host education, which can be used to help the tournament hosts with their aim of creating a good tournament experience, both for the foreign teams and themselves.The essay’s experience production perspective is based on my own prior knowledge of the subject, combined with the results of gathered empirical research. From this, it was concluded that location, interaction and hostmanship is of great importance for the overall experience of the team hosts during Piteå Summer Games. Hopefully, the host education, together with the concept model, will help the team hosts to create a good experience of the tournament for themselves and the visiting teams. By giving the team hosts the possibility to actively enhance their own, as well as the teams’ experiences of Piteå Summer Games, there is the possibility that this concept model will contribute to the return to the tournament of both team hosts and foreign teams. Validerat; 20140617 (johsod)